Knowledge, Attitude, and Practice Related to Diabetes Mellitus Among Diabetics and Nondiabetics Visiting Homeopathic Hospitals in West Bengal, India. (January 2016) - Koley, Munmun; Saha, Subhranil; Arya, Jogendra Singh; Choubey, Gurudev; Ghosh, Shubhamoy; Chattopadhyay, Rajat; Das, Kaushik Deb; Ghosh, Aloke; Hait, Himangsu; Mukherjee, Rajarshi; Banerjee, Tanapa
High prevalence of undiagnosed cases of diabetes mellitus and poor knowledge, awareness, and practice has increased premature death, costly complications, and financial burden. A cross-sectional survey was conducted in November 2014 on 273 diabetics and 355 nondiabetics in 3 government homeopathic hospitals in West Bengal, India. A self-administered questionnaire assessing knowledge, awareness, and practice related to diabetes was used. A total of 17.5% to 29.3% of the participants were aware of the normal blood sugar level. Lack of insulin, frequent urination, hypertension, and poor wound healing were identified most frequently as the cause, symptom, association, and complications. A total of 35.5% to 46.5% said that diabetes was preventable; 14.1% to 31.9% knew that diabetes was controllable rather than curable. Consumption of planned diet, avoiding sugar, and testing blood sugar were the most frequently identified components of healthy lifestyle, diabetic diet, and diagnostic domain. Diabetics had higher knowledge and awareness than nondiabetics ( P < .0001); still the latter need to be made aware and knowledgeable to curtail the ever-increasing burden of diabetes.